Porphyra : Harvesting gold from the sea - Sahoo, Dinabandha; Levine, Ira A (New Delhi : I K, 2010)
Introduces Porphyra/Nori farming as a socio-economic development driving force. This book aims to be reference tool for Porphyra cultivation and a teaching guide for aquaculture extension agents. It supplies coherent instructions for the assembly and maintenance of a Nori production system, as well as information about harvesting and product preservation.
Includes index 93p.
Keywords: Harvesting gold from the sea; Porphyra; Technology; Botany